Penerapan Model Contextual Teaching and Learning dengan Mengunakan Alat Peraga Instalasi Listrik Sederhana untuk Meningkatkan Kemampuan Penalaran Siswa pada Materi Logika di Kelas X Multimedia SMK Negeri 5 Singkawang - Nurlita nurlita (LPD IKIP PGRI Pontianak, 2023)
Students reasoning abilities in learning mathematics are still low especially in class X Multimedia SMK Negeri 5 Singkawang. This research was conducted based on the lack of reasoning levels of some students in learning mathematics, therefore the researchers tried to overcome these problems in learning mathematical logic. Problems that can be identified are as follows, 1) students' reasoning abilities are lacking, 2) learning models are less effective and previous learning does not use learning media. The purpose of this study was to improve students' reasoning abilities on logic material in class X Multimedia SMK Negeri 5 Singkawang using the CTL (Contextual Teaching and Learning) learning model equipped with simple electrical installation logic demonstration media. The subjects of this study were students of class X Multimedia where the number of students was 36 students. This classroom action research procedure consisted of 2 cycles, each cycle consisting of 1 meeting consisting of 3 x 45 minutes. From the process of the stages in the research that has been carried out, it is evident that the application of the Contextual Teaching and Learning (CTL) learning model used in learning mathematical logic material by using the help of simple electrical installation logic aids can improve student learning reasoning which was originally a completeness level of 13.89% to 80.5% in cycle I while in cycle II to 100% and can also improve the learning process, which was originally still low to be good in cycle I and in cycle II to be very good. The use of the Contextual Teaching and Learning (CTL) learning model is complemented by learning media in the form of simple electrical installation logic props capable of increasing students' reasoning on logic material in class X multimedia at SMK Negeri 5. This is proven that the average value of individual test results in cycle I was 74.72 with 80.5% classical completeness. whereas in cycle II the average value of individual test results increased by 91.67 with classical completeness of 100%.